Training Report: Capacity Building in Entrepreneurial and Business Skills for Operationalizing Fresh Cassava Roots Packhouse - Nyamutoka, Pamela; Wanda, Kelly; Matovu, Moses; Kwagala, Innocent; Muyinza, Harriet; Kaliisa, Robert; Menya, Geoffrey; Nuwamanya, Ephraim; Nyakaisiki, Elizabeth; Nanyondo, Rose; Abass, Adebayo (The CGIAR Research Program on Roots, 2017)
Cassava is an important source of food and income in Uganda. Consumption of cassava has been increasing especially in the urban areas. Market demand for fresh cassava in 2013 was estimated to be 309,528 MT per annum in 2013. It was projected to increase by 25% to 387,074 MT in 2018 (RTB-ENDURE-Cassava scoping study, 2014). New market segments for fresh cassava roots have been emerging for both niche and mass markets. Fresh cassava was found to be consumed in various forms. According to findings from the Market Study 2015 high-end restaurants had introduced cassava recipes. Fried cassava chips were a delicacy in road-side food catering services, a new phenomenon in urban areas. Further, analysis of respondent responses revealed that the most preferred consumption form was fried (37%), followed by boiled (35%) and steamed in banana leaves (25%). Cassava enjoys a unique position as a convenient food that is easy and fast to prepare. It is in recognition of this, among others, that cassava has been selected as one of the 10 priority crops with a high potential to transform the agricultural sector in Uganda through provision of household food security, incomes, and employment. . However, despite a growth in demand, both the utilization and income derived from marketing of fresh cassava roots are being hindered by the rapid postharvest physiological deterioration (PPD) that causes spoilage of cassava roots within two to three days of harvest. The implication is that it cannot be marketed over a long time and distance, thereby reducing incomes and food security to growers, consumers and traders. This in turn leads to less investments and hence low productivity.To address this challenge, the RTB-ENDURE Cassava sub-project also known as “Extending the Shelf life of Fresh Cassava Roots for Increased Incomes and Postharvest Loss Reduction” aimed at introducing, testing, validating the efficacy of two technologies for increasing the shelf-life of fresh cassava roots, and thereby assisting to increase the value to growers, traders and consumers along the entire value chain. These technologies included high relative humidity storage and waxing. This research also focused on investigating and establishing the business cases for the two technologies in Uganda since both technologies are in commercial use elsewhere but the commercial applicability and viability of the new technologies in Uganda was unknown. The next phase of the project, following on-station research and user validation therefore was to determine the commercial and institutional feasibility of these technologies in Uganda.In doing so, the project proposed to set up two packhouses in order to test their commercial viability. They included one packhouse managed by farmers and another managed by an entrepreneur. To facilitate the successful commercial operations of the packhouses, it was necessary to build the entrepreneurial and business skills of the operators. This report describes the capacity building process and activities that were done to enhance the business and entrepreneurial skills of packhouse operators.